Relación de las habilidades blandas y competencias investigativas de los estudiantes de la Facultad de Ingeniería de Sistemas e Informática de la Universidad Nacional de la Amazonía Peruana Iquitos 2023 - Bardales Pacaya, Sintia Maria (2025)
The purpose of this research was to determine the relationship between soft skills and research competencies of students of the Faculty of Systems Engineering and Computer Science of the National University of the Peruvian Amazon Iquitos 2023. It was carried out through a basic study type and quantitative approach, non-experimental design, cross-sectional. The study population was considered 415 students, and as a sample, 180 students were calculated under the statistical formula for known populations, the sampling was non-probabilistic for convenience. Having as data collection techniques the survey, to measure the variables, two questionnaires were used, one for each variable. And the data were processed using programs such as Microsoft Excel and SPSS V. 25. For the inferential analysis, the normality of the distribution of the data obtained through the application of the instrument was first checked, subsequently, the decision was made to use non-parametric statistics, being pertinent the use of Spearman's Rho statistic. The results indicate a significant, direct, and moderately strong relationship between the variables, with a coefficient of 0.490 and a significance level of 0.000. Therefore, it is concluded that soft skills and research competencies are related among students in the Faculty of Systems Engineering and Computer Science at the National University of the Peruvian Amazon in Iquitos.